A simple model of optimal exploration for oil: Part 1 - Christophe Deissenberg (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1980)
Based on empirical evidence, a simple model of oil exploration and discovery is deyeloped, which emphasizes the stochastics of the discovery process and its informational aspects. Open-loop-feedback, m-measurement-feedback and closed-loop optimal exploratory strategies are derived. In forthcoming Part II, the model behaviour when interfaced with a market mechanism will be analysed.
Keywords: 330; Natural resources; oil exploration; stochastic control; Bayesian analysis